Estudo de viabilidade de exportação de usina de asfalto para a África do Sul - Torres, Pedro Henrique Carrer (My University, 2019)
The present work is about the viability study of exportation of asphalt plants to South Africa. Therefore, firstly, the general data of the manufacturer of the product in question had been collected in order to obatin as much information as possible. Posteriorly, were analyzed aspects that should be considered to assess whether or not it is feasible to export a particular product or service to a foreign market, such as the analysis of the company's export capacity; issues that must be considered when analyzing supply and demand for the product in the market; analysis of the potential competitiveness of the company; and, finally, the verification of the target market entry strategy. After surveying all costs for the installation of an asphalt plant in South Africa, it has been found that exporting an asphalt plant to that country is viable. From this finding, an insertion plan was elaborated focused on the South African market, with the purpose of making exportable.(sic)
O presente trabalho apresenta uma análise da viabilidade de exportação de usinas de asfalto para a África do Sul. Para tanto, primeiramente foram levantados dados gerais da empresa fabricante do produto em questão, a fim de se obter o maior número possível de informações da mesma. Posteriormente, foram estudados aspectos que devem ser considerados para avaliar se é ou não viável a exportação de determinado produto ou serviço para um mercado estrangeiro, como a realização da análise da capacidade exportadora da empresa; questões que devem ser consideradas no momento da análise da oferta e da demanda pelo produto no mercado; análise da potencial competitividade da empresa; e, por fim, a verificação da estratégia de ingresso no mercado-alvo. Após o levantamento de todos os custos para colocação de uma usina de asfalto na África do Sul, verificou-se que a exportação de usina de asfalto para o referido país é viável. A partir dessa constatação, elaborou-se um plano de inserção focado no mercado da África do Sul, com propósito de viabilizar a exportação.(sic)
Keywords: Exportação; Asfalto; Comércio internacional - África do Sul